Colonial Microcystis’ biomass affects its shift to diatom aggregates under aeration mixing - Xiaodong Wang; Xuan Che; Jian Zhou; Boqiang Qin; Xiangming Tang; Ziqiu Liu; Xingguo Liu (Scientific Reports, 2024)
Abstract The effect of hydrodynamic mixing on controlling Microcystis blooms or changing the algal community to diatom dominance has been widely studied; however, the effects of colonial Microcystis biomass on the development of the algal community are poorly known. Here, in order to study the changes in Microcystis blooms under continuous aeration mixing, an experiment was carried out in a greenhouse with factors of varying biomass of Microcystis and inorganic nitrogen and phosphorus enrichment in summer. There were three chlorophyll a (Chl-a) levels in six treatments: low Chl-a level of 68.4 μg L-1 (treatments L, L-E), medium Chl-a level of 468.7 μg L-1 (treatments M, M-E), and high Chl-a level of 924.1 μg L-1 (treatments H, H-E). Treatments L-E, M-E and H-E were enriched with the same inorganic nitrogen and phosphorus nutrients. During the experiment of 30 days, the concentration of Microcystis and Chl-a decreased, and diatom Nitzschia palea cells appeared in all the treatments, which became dominant in treatments M, M-E, H and H-E, with the highest biomass of 9.41 ± 1.96 mg L-1 Nitzschia in treatment H-E on day 30. The rank order of the biomass of Nitzschia from low to high was (L = L-E) < (M = M-E) < H < H-E (P < 0.05). In addition, Nitzschia cells were aggregates attached to Microcystis colonies in all the treatments. The results showed that the initial biomass of colonial Microcystis affected the algal shift from Microcystis dominance to Nitzschia dominance. However, the enriched inorganic nitrogen and phosphorus was beneficial for the Nitzschia increase in the high biomass treatment alone. The shift from Microcystis dominance to diatom dominance under continuous aeration mixing may be caused by low light conditions as well as the nutrients released from Microcystis decay. Moreover, the aerobic condition caused by aeration mixing maintained the colonial mucilaginous sheath to support the growth of Nitzschia cells in aggregation. This study found for the first time that Microcystis blooms could shift to diatom Nitzschia dominance in aggregates. It provided a method to control and manipulate Microcystis blooms to diatom dominance through continuous aeration mixing to proper biomass of Microcystis colonies. The shift to diatoms dominance would provide more high quality food organisms for aquaculture and be beneficial to the material cycling and energy flowing in food web dynamics.